PEMANFAATAN INTERNET DAN JEJARING SOSIAL UNTUK PEMBELAJARAN DI MADRASAH ALIYAH (MA) NURUL FURQOON KECAMATAN BINJAI BARAT KOTA BINJAI - Yusuf, Kadri; Prayudani, Santi; Julham, Julham (STMIK KAPUTAMA, 2020)
The development of science and technology, especially information and communication technology (ICT) has penetrated various fields of life including education and teaching. The progress of ICTs is undeniably a lot of positive impacts on the progress of today's education world. Social networking or friendship through the Internet, otherwise known as social networking, is also experiencing rapid growth. The trend of using social networking is actually an interesting opportunity to be utilized as one of the learning media. Utilization of the internet and social networking in learning in Madrasah Aliyah (MA) Nurul Furqoon Binjai is an effort to improve teacher efficiency so that it is more focused on improving the quality of learning by providing training on the use of Whatsapp, Teamviewer and Google Drive. in facilitating teachers in undergoing the process of teaching and learning in schools. It is expected that by knowing the function of social media, teachers can easily and quickly transfer information to students or to teachers at Madrasah Aliyah (MA) Nurul Furqoon schools.